Νέοι εκπαιδευτικοί, νέες συνθήκες και νέα εργαλεία για την εκπαίδευση παιδιών με μεταναστευτικό και προσφυγικό υπόβαθρο - Μακρογιάννη, Τσαμπίκα; Κούρτη-Καζούλλη, Βασιλεία (Παιδαγωγικά ρεύματα στο Αιγαίο, 2024)
The main objective of the Language Curriculum is to make the educational system responsive to the new conditions that have emerged in schools. Considering the requirements of the Curricula, new learning tools were used in this research and were applied in the context of language teaching at primary schools at the Department of Primary Education, University of the Aegean. These tools included a combination of theories, i.e. Cummins' (2005) theory for the development of Academic Language Proficiency, approaches about New Learning (Kalantzis & Cope, 2005) and Transformative Pedagogy (Cummins, 2005; Kalantzis & Cope, 2013). The aim of the research was for future teachers to learn how to support the multilingual students in schools in critically processing the diverse textual types in the language lessons, thereby achieving both the development of linguistic and communicative competence and the interaction of the school community with the wider society.